Analisis Kesalahan Berbahasa Tataran Sintaksis dalam Kumpulan Makalah Mahasiswa Universitas Islam Riau - Alber, Alber; Febria, Rhani (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
Analysis of language errors is the science of studying or discussing the use of languages that are notin accordance with the rules that have been determined based on standard grammar, these are stillfound in scientific works including in a collection of scientific papers of students of IslamicUniversity of Indonesia Language and Literature Study Program. The language used by students issometimes not in accordance with the rules of language contained in the Indonesian SpellingGeneral Guidelines (PUEBI). Therefore, this research was conducted with the aim of analyzing andinterpreting errors in syntactic level language, phrase fields and sentences in a collection ofscientific papers by students of the Islamic University of Riau Indonesian Language and LiteratureStudy Program. This study uses the content analysis method that is prescriptive. Data collectiontechniques using documentation and hermeneutic techniques. The data of this study are sourcedfrom a collection of scientific papers from students at the Islamic University of Riau FKIPIndonesian Language and Literature Study Program. The data studied was documented by reading,taking notes and then concluded and grouped based on the use of each level. Errors in language in acollection of student papers at the Islamic University of Riau FKIP Indonesian Language andLiterature Study Program found language errors at the syntactic level. The results of this study, thephrase field errors are excessive or redundant use of elements and improper use of prepositions.Meanwhile, language errors in the sentence field include, the sentence is not subject, the sentence isnot predicated, the sentence is not subject and is not predicated/sentence stumps such as the use ofwords, illogical sentences, excessive use of conjunctions, non-parallel sequences, use of foreignterms , and the use of unnecessary question words.